1988
DOI: 10.1007/bf00339686
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis and corpus callosum atrophy: Relationship of MRI findings to clinical data

Abstract: Among 110 patients (45 men, 65 women), aged 15 to 66, with clinical and/or biological diagnosis of multiple sclerosis (MS), severe to moderate corpus callosum (CC) atrophy was observed in 67 (60%) patients. Correlation between CC atrophy, brain atrophy, duration and severity of clinical symptoms, and high signal white matter areas, was carried out in 90 patients. Mean age was 46 years for patients with severe CC atrophy, and 33 years for those without atrophy. Mean duration of the disease was 14 years in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 4 publications
3
19
1
Order By: Relevance
“…Although brain atrophy in multiple sclerosis (MS) has been demonstrated with initial imaging and histopathologic reports of enlarged ventricles (1,2) and reduced size of corpus callosum (3), there is much current interest in the accurate and precise quantification of brain atrophy in MS by developing and improving quantitative magnetic resonance (MR) imaging techniques (4 -6). The combination of advanced computer-assisted techniques and high-spatial-resolution MR imaging has allowed measurement of the amount of the brain tissue loss during the course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although brain atrophy in multiple sclerosis (MS) has been demonstrated with initial imaging and histopathologic reports of enlarged ventricles (1,2) and reduced size of corpus callosum (3), there is much current interest in the accurate and precise quantification of brain atrophy in MS by developing and improving quantitative magnetic resonance (MR) imaging techniques (4 -6). The combination of advanced computer-assisted techniques and high-spatial-resolution MR imaging has allowed measurement of the amount of the brain tissue loss during the course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Autopsy and MRI studies indicate that atrophy of corpus callosum (CC) is a common finding in patients with MS. [14][15][16][17][18][19][20][21][22][23][24] Demyelinating lesions of callosal or subcallosal areas found in most patients with MS could ex-plain CC atrophy. 17,20 However, some studies demonstrated dysfunction of interhemispheric transfer in patients with MS, particularly on verbal dichotic listening tasks showing a left-ear dichotic suppression. 18,22,[25][26][27] Functional impairment of interhemispheric transfer in MS has also been correlated to the degree of callosal atrophy and to the severity and diffusion of white matter changes identified by MRI.…”
Section: Original Contributionmentioning
confidence: 99%
“…[18] As the disease progresses, the corpus callosum undergoes atrophy and becomes thinned out. [19] Amongst the newer techniques, diffusion tensor tractography can demonstrate degree of axonal loss in the regions of white matter lesions, including the corpus callosum, extremely well. [20]…”
Section: Introductionmentioning
confidence: 99%